Dampak Variabel Makroekonomi Terhadap Nilai Aktiva Bersih (NAB) Reksadana Syariah Menggunakan Metode Regresi Data Panel - Muhammad Dedat Dingkoroci Akasumbawa; Abdul Qoyum (Riset, Ekonomi, Akuntansi dan Perpajakan (Rekan), 2023)
This study aims to examine the relationship between macroeconomic variables, namely inflation, rupiah exchange rate, gross domestic product, money supply, and interest rates on the Net Asset Value (NAV) of Islamic Mutual Funds. The sampling method used purposive sampling with 9 mutual fund companies from 2013 to 2020. This study used a panel data regression method with a random effect model. The results showed that inflation and interest rates did not show any effect on the NAV of Islamic Mutual Funds. There is no effect on inflation because the inflation rate in Indonesia is still at a low level. The interest rate has no effect because the character of mutual funds is a long-term investment instrument. The money supply and the exchange rate have a significant positive effect on the NAV of Sharia Mutual Funds. This is due to the increase in the money supply and the rupiah exchange rate from year to year. Meanwhile, gross domestic product has a significant negative effect on the NAV of Sharia Mutual Funds. This is because the NAV of mutual fund companies from year to year depreciates, while gross domestic product from year to year appreciates.